2014
DOI: 10.7241/ourd.20142.27
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of peroxisome proliferators – activated receptor γ gene expression in inflammatory skin diseases: atopic dermatitis and psoriasis

Abstract: Introduction: Psoriasis is a genetically determined chronic disease of skin in which a number of biochemical alterations take place during its course. The main objectives of our study were to calculate various biochemical parameters in psoriasis correlate them clinically. Materials and Methods: An attempt was made to detect the biochemical changes during its exacerbations. Fifty biopsy proved psoriasis patients were selected. Clinical examination and the various biochemical tests were performed at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Inflammation and an altered epidermal barrier function are characteristics of dermatitis of any origin and researchers Arch Dermatol Res after observing deranged PPAR expression in various dermatitic conditions including atopic dermatitis (AD) suggested their significant role in the pathogenesis of dermatitis [13,17,51]. Chiba et al [13] observed downregulation of PPARa in atopic dermatitis (AD)-like dermatitis in nc/Nga mice.…”
Section: Dermatitismentioning
confidence: 97%
See 1 more Smart Citation
“…Inflammation and an altered epidermal barrier function are characteristics of dermatitis of any origin and researchers Arch Dermatol Res after observing deranged PPAR expression in various dermatitic conditions including atopic dermatitis (AD) suggested their significant role in the pathogenesis of dermatitis [13,17,51]. Chiba et al [13] observed downregulation of PPARa in atopic dermatitis (AD)-like dermatitis in nc/Nga mice.…”
Section: Dermatitismentioning
confidence: 97%
“…Chiba et al [13] observed downregulation of PPARa in atopic dermatitis (AD)-like dermatitis in nc/Nga mice. Atopic dermatitis lesional skin shows nearly 50 % reduction in PPARa expression in comparison to normal skin, and down-regulation of PPARa by influencing the lipid pathway is perhaps involved in development or maintenance of atopic dermatitis [51]. An increased expression of PPARa has been observed in a mouse model of allergic contact dermatitis and PPARa ligands reduce epidermal hyperproliferation and stimulate differentiation.…”
Section: Dermatitismentioning
confidence: 98%
“…The important role of epidermal PPARγ in moderating cutaneous inflammation is seen both by analysis of the differentially expressed genes as well as the observed phenotype. The top GO terms that linked to our data set showed upregulation of multiple inflammatory cytokine and chemokine transcripts, upregulation of genes associated with inflammasome activation (Aim2, Nod2, Nlrp3, Il1f6 and 8, Casp1, Gsdma2, Gsdmc), and the upregulation of keratins associated with inflammatory hyperplasia (e.g., Krt 6,16,17). In addition to the disruption in inflammatory signaling, C57.Pparg-/-epi mice developed spontaneous lesions that are reminiscent of wound healing, atopic dermatitis, and psoriasis.…”
Section: Discussionmentioning
confidence: 97%
“…There is strong evidence that PPARγ may suppress the inflammation associated with inflammatory dermatoses. Relative to normal human control skin, PPARγ transcripts in psoriatic and atopic lesions are reduced 8-and 3.3-fold, respectively [17]. Another study demonstrated that PPARG mRNA is significantly decreased in human lichen planopilaris, a form of scarring (cicatricial) alopecia [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another study confirmed the downregulation of PPARγ in explanted fibroblasts of lesional skin from patients with systemic sclerosis [ 98 ]. In addition, PPARγ has been reported to be downregulated in UV-irradiated damaged skin [ 185 ], in systemic lupus erythematosus patients with skin lesions [ 187 ] and in psoriatic and atopic lesions [ 186 ]. An investigation of 100 acne patients compared to 100 healthy subjects further found that the Pro12Ala polymorphism of the PPARγ gene, which results in decreased PPARγ transcriptional activity, is associated with a lower risk of acne vulgaris [ 196 ].…”
Section: The Endocannabinoid System In the Skinmentioning
confidence: 99%